Kuasa Gereja Memutuskan Ikatan Perkawinan Non-Sakramen - Rubiyatmoko, Robertus (Jurnal Orientasi Baru, 2006)
The Catholic Church constantly teaches that a valid marriage, both sacramental and non sacramental marriage, has a character of indissolubility (cfr. Can. 1056). It does mean that once a man and a woman validly contract a marriage, they are tied by an indissoluble and perpetual bond. Therefore there is no possibility for separation or divorce of the spouses, unless because of death. Jesus said that what God has united, man must not divide (Mrk10:9). But based on the judicial practice of the Church, it is clear that God has given an outhority to the Church to dissolve the matrimonial bond, which is not all at once ratum et consummatum (cfr- Mat 16:18-19; Can. 1142-1149).